Association Between Glycated Hemoglobin (HbA1c) Levels and Mean Platelet Volume (MPV) in Patients with Type 2 Diabetes Mellitus - Aloysia Flower Lula Utami; Nurhasan Agung Prabowo; Berty Denny Hermawati; Desy Puspa Putri; Niken Bayu Argaheni (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by persistent hyperglycemia, which can trigger inflammatory responses contributing to various vascular complications. Inflammation plays a key role in the pathogenesis of DM-related complications through mechanisms involving oxidative stress and activation of NF-κB signaling, which influence platelet production and activity. Given inconsistent findings regarding the association between HbA1c and mean platelet volume (MPV) in previous studies, this study aims to investigate the relationship between HbA1c and MPV, a pro-thrombotic and inflammatory marker, in patients with type 2 diabetes mellitus. This study is an analytical observational study with a cross-sectional approach. Data were collected from the medical records of Universitas Sebelas Maret (UNS) Hospital, Indonesia, using purposive sampling. HbA1c and MPV data were obtained from patients’ medical records over the past year. Statistical analysis was performed using the Shapiro–Wilk normality test and Pearson correlation test. A total of 38 samples were included in the study. The mean HbA1c level was 10.37% (range: 6.50–16.10), while the mean MPV was 9.38 fL (range: 7.30–12.50). Pearson correlation test showed a significant relationship between HbA1c and MPV (r = 0.467; p = 0.003). There is a significant positive correlation between HbA1c and MPV in patients with type 2 diabetes mellitus.